Applying nasal airflow – inducing maneuvers with patients with hyposmia after total laryngectomy - Hamerlińska, Agnieszka (Contemporary Oncology/Współczesna Onkologia, 2019)
The consequence of total laryngectomy is complete loss or disorder of smell. The change may affect daily life and decrease the standard of living of people after larynx removal. A study was carried out in a group of 19 people in order to demonstrate whether applying nasal airflow-inducing maneuvers improves smell. The research was conducted during rehabilitation by the seaside in 2018. The group included 6 women and 13 men. There were two tests. The first was done before presentation of nasal airflow-inducing maneuvers. The group received 10 fragrances and were asked to identify them. Next nasal airflow-inducing maneuvers were presented and a training session was carried out. The second test was performed. According to the analysis of results, in most participants their odor sensation improved, but to different levels. Smell exercise in necessary in rehabilitation of patients after larynx removal. A person who can conduct olfactory therapy can be a speech therapist.